What Matters In Financial Risk Tolerance Level? An Empirical Study In Pakistan - Urooj, Dr. Syeda Faiza; Zafar, Dr. Nousheen; Hassan, Prof Dr. Arshad; Sindhu, Muzammal Ilyas (The journal of contemporary issues in business and government, 2021)
This study is an effort to investigate the relationship between socioeconomic, demographic factors and the individual’s financial risk tolerance level in investment decisions. Various actors like gender, age, income, education, and nature of work of individuals have been assessed to find their financial risk tolerance level in investment decisions. The sample data has been gathered from the individual investors of Karachi Stock Exchange (KSE), Islamabad Stock Exchange (ISE) and Lahore Stock Exchange (LSE) through the questionnaire designed by Dow Jones and Company in 1998. Various research techniques like descriptive statistics, univariate analysis, correlation analysis, and multivariate regression has employed in order to investigate different factors that matter in individuals' financial risk tolerance level. The results reveal that in the case of Pakistan male investors dominate the investment market implying a higher level of financial risk tolerance in men compared to women. Mostly investors possess higher education like graduation and above due to which financial risk tolerance increases with higher qualification. Increase in age results in an increase in the level of investor’s financial risk tolerance and increase in the income level of individuals also increases the level of financial risk tolerance of the individuals in investment decisions in the context of Pakistan.